2004
DOI: 10.1111/j.1472-765x.2004.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Some potential sources for transmission of Campylobacter jejuni to broiler chickens

Abstract: Aims: The aim of the study was to determine Campylobacter jejuni contamination and prevalence on fomites moving between broiler farms and the processing plant in the period after cleaning and before departure to harvest chickens. In addition, changes in the proportion of contaminated fomites in the course of a day were assessed. Methods and Results: Pooled swab samples were obtained from pallets, crates, wheels of trucks, tractors and forklifts, truck beds, and from drivers' and catchers' boots. After enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Farm staff handling of other neighboring livestock, especially poultry, increases the risk of Campylobacter-positive flocks, and both the number of staff members looking after the house and the number of visits they undertake per day are directly related to that risk (41,68). Campylobacters have been isolated from the clothes, hands, and boots of farm staff, managers, catchers, and lorry drivers (38,66), and molecular epidemiology provides evidence that these strains are often subsequently associated with flock colonization (38,46,71,72). It seems likely, therefore, that people entering the poultry house can track in campylobacters from the external environment.…”
Section: Resultsmentioning
confidence: 99%
“…Farm staff handling of other neighboring livestock, especially poultry, increases the risk of Campylobacter-positive flocks, and both the number of staff members looking after the house and the number of visits they undertake per day are directly related to that risk (41,68). Campylobacters have been isolated from the clothes, hands, and boots of farm staff, managers, catchers, and lorry drivers (38,66), and molecular epidemiology provides evidence that these strains are often subsequently associated with flock colonization (38,46,71,72). It seems likely, therefore, that people entering the poultry house can track in campylobacters from the external environment.…”
Section: Resultsmentioning
confidence: 99%
“…Personnel and farm equipment such as trucks, forklifts, pallets, crates, and footwear have also been identified as potential sources of C. jejuni infection of broilers (Ramabu et al 2004). Farm vehicles are often contaminated with 92 HERMANS ET AL.…”
Section: Sources For Horizontal Campylobacter Transmission To Broilermentioning
confidence: 99%
“…Transport cages are known to become highly contaminated with feces and bacteria during the process of transport [8][9][10][11][12][13]. Ramabu et al [14], in a study of Campylobacter contamination within the broiler poultry production environment, found that after transport, poultry crates were contaminated at a rate of 75%, while 47% of truck beds were also contaminated. This phenomenon has been associated with the contamination of flocks as they enter the processing plant [15][16][17].…”
Section: Introductionmentioning
confidence: 98%